A systematic review and meta‐analysis of randomised controlled trials of surgical treatments for ingrown toenails part II: healing time, post‐operative complications, pain, and participant satisfaction - Victoria Exley; Katherine Jones; Grace O'Carroll; Judith Watson; Michael Backhouse (Journal of Foot and Ankle Research, 2023)
Abstract Background When performing nail surgery, clinicians must choose from a multitude of procedures and variations within each procedure. Much has been published to guide this decision making, but there are a lack of up to date robust systematic reviews to assess the totality of this evidence. Methods Five databases (MEDLINE, Embase, CINAHL, Web of Science and CENTRAL) and two registers (Clinicaltrials.gov and ISRCTN) were searched to January 2022 for randomised trials evaluating the effects of a surgical intervention(s) for ingrown toenails. Two independent reviewers screened records, extracted data, assessed risk of bias and certainty of evidence. Data on co‐primary outcomes of symptom relief and symptomatic regrowth were presented in our first paper. This paper presents data for the secondary outcomes and further discussion. Results Of 3,928 records identified, 36 randomised trials were included in the systematic review. Healing time appears to be reduced with shorter application of phenol. A reduced healing time was also apparent was with the addition of curettage, although this may also increase the risk of post‐operative bleeding and pain. Post operative bleeding was also reportedly lower in people who received local anaesthetic with epinephrine but no tourniquet. Use of phenol with nail bed excision may decrease the risk of infection. Lower pain scores were reported when using partial matrixectomy and surgical interventions with phenol. Shorter duration of pain was reported with phenolisation and wedge resection. Participant satisfaction was high overall. Conclusion This second paper reports secondary outcomes from a robust systematic review of randomised trials on surgical treatment of ingrown toenails. Despite the large volume of clinical trials conducted on the topic, few clinical conclusions can be drawn due to the poor quality of these studies. Further high‐quality clinical trials are needed to answer fundamental questions in the surgical treatment of ingrown toenails.